Biological Tissues as Active Nematic Liquid Crystals. Issue 47 (29th August 2018) - Saw, Thuan Beng; Xi, Wang; Ladoux, Benoit; Lim, Chwee Teck
Abstract: Live tissues can self‐organize and be described as active materials composed of cells that generate active stresses through continuous injection of energy. In vitro reconstituted molecular networks, as well as single‐cell cytoskeletons show that their filamentous structures can portray nematic liquid crystalline properties and can promote nonequilibrium processes induced by active processes at the microscale. The appearance of collective patterns, the formation of topological singularities, and spontaneous phase transition within the cell cytoskeleton are emergent properties that drive cellular functions. More integrated systems such as tissues have cells that can be seen as coarse‐grained active nematic particles and their interaction can dictate many important tissue processes such as epithelial cell extrusion and migration as observed in vitro and in vivo. Here, a brief introduction to the concept of active nematics is provided, and the main focus is on the use of this framework in the systematic study of predominantly 2D tissue architectures and dynamics in vitro. In addition how the nematic state is important in tissue behavior, such as epithelial expansion, tissue homeostasis, and the atherosclerosis disease state, is discussed. Finally, how the nematic organization of cells can be controlled in vitro for tissue engineering purposes is briefly discussed. Abstract : Tissue architecture and dynamics in vitro can be described in terms of active nematics, which allows a deeper understanding of phenomena such as epithelial expansion and tissue homeostasis, and enables better tissue‐engineering design. The image shows the three typical cellular arrangements within an epithelium, i.e. aligned region, comet defect, and triangle defect.